Detecting Predeath Grief in Family Caregivers of Persons With Dementia: Validity and Utility of the Marwit-Meuser Caregiver Grief Inventory in a Multiethnic Asian Population - Liew, Tau Ming (OXFORD UNIV PRESS INC, 2022)
10.1093/geront/gnx097